2021
DOI: 10.1186/s12986-021-00631-7
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating the effect of quinoa and the underlying mechanism on hepatic steatosis in high-fat diet-fed rats

Abstract: Background Nonalcoholic fatty liver disease (NAFLD) is considered the hepatic component of metabolic syndrome and has attracted widespread attention due to its increased prevalence. Daily dietary management is an effective strategy for the prevention of NAFLD. Quinoa, a nutritious pseudocereal, is abundant in antioxidative bioactive phytochemicals. In the present study, the effects of different amounts of quinoa on the progression of NAFLD and the related molecular mechanism were investigated. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
2
4
0
Order By: Relevance
“…The observed improvement in liver morphology was independent of hepatic TG content, which was not significantly different between PEP2 and HFD groups, but a decrease in cholesterol content was seen between HFD and PEP2 groups, similar to Song et al [ 36 ], who reports a reduction of the hepatic total cholesterol content after quinoa supplementation but no difference between HFD and quinoa supplemented groups in terms of hepatic TG [ 36 ] and attributes the improvement in NAFLD in part to changes in hepatic phospholipids, such as increased lysophosphatidylcholine and pantothenic acid, and decreased phosphatidylcholine and dioleoylphosphatidylcholine [ 36 ]. Indeed, impairment of cholesterol metabolism may be the key driver to large LD formation, rather than TG metabolism [ 20 ].…”
Section: Discussionsupporting
confidence: 88%
“…The observed improvement in liver morphology was independent of hepatic TG content, which was not significantly different between PEP2 and HFD groups, but a decrease in cholesterol content was seen between HFD and PEP2 groups, similar to Song et al [ 36 ], who reports a reduction of the hepatic total cholesterol content after quinoa supplementation but no difference between HFD and quinoa supplemented groups in terms of hepatic TG [ 36 ] and attributes the improvement in NAFLD in part to changes in hepatic phospholipids, such as increased lysophosphatidylcholine and pantothenic acid, and decreased phosphatidylcholine and dioleoylphosphatidylcholine [ 36 ]. Indeed, impairment of cholesterol metabolism may be the key driver to large LD formation, rather than TG metabolism [ 20 ].…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, impaired insulin sensitivity is associated with dysfunction of the pancreas islets (Sampey et al, 2011) and slightly hypertrophic and disfigured pancreatic islets with dramatically distorted architecture in cafeteria-fed rats were shown (Sampey et al, 2011). An inverse relationship between quinoa supplementation and body weight gain has been reported previously, in studies using high-fat diets as an obesity model (Cao et al, 2020;Song et al, 2021). Our results showed similar effects as CAFQ displayed an attenuated body weight in comparison with CAF.…”
Section: Discussionsupporting
confidence: 86%
“…A number of animal studies have verified the hepatoprotective potential of adding quinoa to energy‐dense diets (Ng & Wang, 2021 ) by reducing hepatic lipid accumulation (An et al, 2021 ; Song et al, 2021 ). Also, lower levels of lipid aggregation in the liver (Noratto et al, 2019 ), decreased hepatic fat (Gewehr et al, 2016 ) protected liver tissue structure (Obaroakpo et al, 2020 ) were reported in rodents due to quinoa (Noratto et al, 2019 ), quinoa flakes (Gewehr et al, 2016 ), or sprouted quinoa yoghurt (Obaroakpo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Song et al administered different amounts of quinoa in a high-fat diet to rats to assess their effects on nonalcoholic fatty liver disease. They concluded that both lower and higher quantities of quinoa could effectively regulate the lipid profile, control the body weight, and mitigate oxidative stress; besides, a high quantity of quinoa upregulated genes related to lipid metabolism (32). Moreover, in a study by Li et al , after four weeks of quinoa bread consumption, the level of low-density lipoprotein-cholesterol (LDL-C) was found to be significantly lower than the baseline; however, there was no significant difference between the quinoa and control groups (15).…”
Section: Nutritional Valuementioning
confidence: 99%